Is There Such a Thing as a Family Constitution? : A Test Based on Credit Rationing - Alessandro Cigno; Gianna Claudia Giannelli; Furio C. Rosati; Daniela Vuri (Institute for the Study of Labor (IZA), 2004)
The paper aims to ascertain whether voluntary money transfers may be explained by the existence of self-enforcing family constitutions. We identify a circumstance in which an agent will behave differently if she is optimizing subject to a family constitution, than if she is moved by either altruistic or exchange motivations. The circumstance is the presence of a binding credit ration, which may raise the probability of making a money transfer (and the amount of money transferred) if a family constitution exists, but will have the opposite effect if the transfer is either a gift, or payments for services rendered. Allowing for possible endogeneity, we find that rationing has a positive effect on the probability of giving money, and on the amount given, if the potential giver is under the age of retirement and has children, but no significant effect if the person has no children, or is over the retirement age. This rejects the hypothesis that money transfers are motivated by either altruistic or straight exchange motives, but not the one that these transfers are governed by family constitutions.
Keywords: J14; J13; D13; 330; family constitution; altruism; exchange; private transfers; personal services; Privater Transfer; Familiensoziologie; Altruismus; Hausarbeit; Familienökonomik; Kreditrationierung; Theorie; Schätzung; Italien